PENERAPAN PEMBELAJARAN INKUIRI DALAM MATERI PENGHANTAR PANAS UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA SISWA KELAS VI SDN JAMBUWER 02 KAB. MALANG TAHUN AJARAN 2016/2017 - Emmy Suaida (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2017)
Learning IPA at SD Negeri Jambuwer 02 Kab. Malang still use the less innovative learning model, so that students are not active. This causes the students passive and low learning outcomes. The Inquiry Strategy Learning is one solution to resolve the issue. This research aims to find out whether inquiry learning can increase the activity of learning and learning outcomes. Classroom Action Research goal is to describe the application of the Inquiry Strategy Learning to determine the learning outcomes of students in IPA. This study lasted for two cycles. Data collection tool that is used is observation, tests, and documentation. Analysis of the data in this class action research using descriptive analysis. Based on the observation in cycle 1 can be conclude that the learning activity increased about 30% and in cycle 2 increased about 50%. And meanwhile the students learning outcome can be describe, that the students passing studying in cycle 1 was 56% (pass) increased in cycle 2 became 86% (pass). From the result of this research it can be concluded that the implementation of inquiry strategy learning can increase the student learning activity and the student learning outcomes in SD Negeri Jambuwer 02, Kabupaten Malang.